2003
DOI: 10.1038/sj.jhh.1001506
|View full text |Cite
|
Sign up to set email alerts
|

Isolated systolic hypertension: data on a cohort of young subjects from a French working population (IHPAF)

Abstract: Elderly patients with isolated systolic hypertension (ISH)Fsystolic blood pressure (SBP) X140 mmHg and diastolic blood pressure (DBP) o90 mmHgFhave increased mortality and morbidity. The aim was to study the incidence of ISH in a younger population of between 15 and 60 years of age, and to measure pulse pressure (PP), mean arterial pressure (MAP) and heart rate (HR) in these subjects. The study population consisted of 27 783 subjects, aged 15-60 years, untreated for hypertension (HT) from a cohort of employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
12
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
6
12
0
2
Order By: Relevance
“…In our study, ISH was detected in 18% of the studied population, being also the predominant form of hypertension (78%). These results are comparable to the French study, in which 60% of young hypertensive men had ISH [12].…”
Section: Discussionsupporting
confidence: 86%
“…In our study, ISH was detected in 18% of the studied population, being also the predominant form of hypertension (78%). These results are comparable to the French study, in which 60% of young hypertensive men had ISH [12].…”
Section: Discussionsupporting
confidence: 86%
“…4 However, an elevated PP often associated with isolated systolic hypertension (ISH) may be found also among young individuals, particularly in men, as documented by several studies. [5][6][7][8] The clinical significance of these conditions in youth is still controversial for the obvious necessity of a long-term follow-up to accumulate a sufficient number of hard end points. The first authors who highlighted a different prognostic value of PP according to age were Sesso et al 9 Considering both PP and mean blood pressure (MBP) in the same multivariable survival model, these authors observed that in a general male population, PP had an important predictive capacity for cardiovascular disease only among people aged ≥60 years, whereas among people aged <60 years, PP only had a marginal predictive value.…”
mentioning
confidence: 99%
“…8 Although the mechanisms underlying ISH in younger individuals are poorly understood, two recent reports suggest that exaggerated pulse pressure (PP) amplification may be responsible and, hence, the terms "pseudo" or "spurious" hypertension have been applied. 9,10 However, in both studies, central PP appeared to be elevated in the ISH subjects compared with normotensive individuals, suggesting that ISH in young individuals may not be benign.…”
mentioning
confidence: 99%